2005
DOI: 10.1111/j.1365-2516.2005.01104.x
|View full text |Cite
|
Sign up to set email alerts
|

Thromboelastography measurements of whole blood from factor VIII‐deficient mice supplemented with rFVIII

Abstract: The rotational thromboelastography (ROTEG) assay system allows the real-time analysis of clot formation (fibrin formation) in a whole-blood assay format. The ROTEG system provides significant advantages over the current plasma-based assay systems as it includes the important interactions between cellular and plasmatic coagulation factors. We have employed the ROTEG system to characterize clot formation dynamics in factor VIII- deficient mouse whole blood and examined the ability of recombinant FVIII (rFVIII) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 22 publications
(29 reference statements)
2
17
0
1
Order By: Relevance
“…Even if Fg was diminished by 50% (Fg ϩ/Ϫ ) as a result of LPS treatment, the TEG results would have been similar to WT mice ( Figure 5D, Table 1). On the other hand, previous TEG studies on FVIII Ϫ/Ϫ mouse blood have shown abnormal R and K values, 18 which is consistent with our data demonstrating large effects on whole blood clotting with consumption of intrinsic factors. In the case of LPS-treated PC Ϫ/Ϫ PC(tg4)/ TF Ϫ/Ϫ TF(tg) mice, both the FVIII and FIX levels are reduced, exacerbating the abnormal clotting of whole blood.…”
Section: Resultssupporting
confidence: 93%
“…Even if Fg was diminished by 50% (Fg ϩ/Ϫ ) as a result of LPS treatment, the TEG results would have been similar to WT mice ( Figure 5D, Table 1). On the other hand, previous TEG studies on FVIII Ϫ/Ϫ mouse blood have shown abnormal R and K values, 18 which is consistent with our data demonstrating large effects on whole blood clotting with consumption of intrinsic factors. In the case of LPS-treated PC Ϫ/Ϫ PC(tg4)/ TF Ϫ/Ϫ TF(tg) mice, both the FVIII and FIX levels are reduced, exacerbating the abnormal clotting of whole blood.…”
Section: Resultssupporting
confidence: 93%
“…The TEG assay has a greater sensitivity than traditional clotting assays and allows the analysis of clot (fibrin) formation in real time, demonstrating that the rate of fibrin formation correlates to FVIII levels from 0.001% to 100%. 60,61 In these studies, all 8 dogs have maintained clinical chemistry and hematologic parameters within normal limits. No abnormal histopathologic findings were found in liver biopsies.…”
Section: Long-lived Therapeutic Activity In the Absence Of Toxicity Bmentioning
confidence: 99%
“…23 A similar picture is observed in murine blood. Thus, blood from FVIII knockout mice coagulates later than blood from normal mice 18 and after coagulation is initiated, the propagation of the clot formation is slower. When comparing the data from the mice with a normal coagulation system and FVIII knockout mice the thromboelastographic analysis revealed …”
Section: Discussionmentioning
confidence: 99%
“…16 Thus, the clotting process is significantly impaired in blood from haemophilic patients (and animals) compared with individuals with a normal coagulation system. 17,18 However, because blood coagulation initiates as soon as the blood is drawn from the vessel or gets in contact with intravascular tissue, the result of the following analysis is very sensitive to the preanalytical conditions such as the blood collection method.…”
mentioning
confidence: 99%